A systematic review and meta-analysis on the efficacy of stem cell therapy on bone brittleness in mouse models of osteogenesis imperfecta - Battle, Lauren (Bone Rep, 2021)
There is no cure for osteogenesis imperfecta (OI), and current treatments can only partially correct the bone phenotype. Stem cell therapy holds potential to improve bone quality and quantity in OI. Here, we conduct a systematic review and meta-analysis of published studies to investigate the efficacy of stem cell therapy to rescue bone brittleness in mouse models of OI. Identified studies included bone marrow, mesenchymal stem cells, and human fetal stem cells. Effect size of fracture incidence, maximum load, stiffness, cortical thickness, bone volume fraction, and raw engraftment rates were pooled in a random-effects meta-analysis. Cell type, cell number, injection route, mouse age, irradiation, anatomical bone, and follow up time were considered as moderators. It was not possible to investigate further parameters due to the lack of standards of investigation between the studies. Despite the use of oim mice in the majority of the investigations considered and the lack of sham mice as control, this study demonstrates the promising potential of stem cell therapy to reduce fractures in OI. Although their low engraftment, cell therapy in mouse models of OI had a beneficial effect on maximum load, but not on stiffness, cortical thickness and bone volume. These parameters all depend on bone geometry and do not inform on its material properties. Being bone fractures the primary symptom of OI, there is a critical need to measure the fracture toughness of OI bone treated with stem cells to assess the actual efficacy of the treatment to rescue OI bone brittleness.